(3EOGQI Gdfbd GdHMQj (B((3GdJLGQI GdNWjI(B) (3aYGdjGJ GdJWHjb (B- (3eJWdHGJ GdQjGOI (B/s - (3eGgQ, TQja eMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2006)
(3GdJLGQI GdYGdejI GdHMQjI,GdeDJeQGJ GdedGMjI hGSJQGJjLjGJ GdJLGQI GdHMQjI,GdLhGfH GdJWHjbjI dYed GdJLGQI GdHMQjI,GdMGhjGJ hCKGQgG Ydi GdJLGQI GdNWjI hGdfbd eJYOO GdhSGFW,bhGYO Sdhc Gdfbd GdHMQj hbQGQGJ TQcGJ GdJLGQI GdNWjI,JfXje TQcGJ GdNOeGJ GdNWjI hYbhO EOGQJgG hJTZjdgG,JShjb GdNOeGJ GdNWjI aj Gdfbd GdHMQj,TQM GdHjhY GdJLGQjI GdOhdjI,JUhQGJ Gdfbd GdHMQj MJi YGe (B2020(3,fXe JHGOd GdeYdheGJ EdcJQhfjG aj eLGd Gdfbd GdeJYOO GdhSGFWs
(3HHdjhZQGajG(B:(3U(B.343-349(3; cTGa GdeUWdMGJ(B:(3U(B.9-10s
Keywords: (3Gdfbd GdHMQjs